MAPPING OF LEADING SECTORS FOR BLUE ECONOMY SUSTAINABILITY IN DONGGALA DISTRICT: A QUALITATIVE APPROACH AND LOCATION QUOTIENT ANALYSIS - Dewi Halifah; Widyastuti; Iwan Alim Saputra; Arifuddin Abd Muis (Universitas Negeri Surabaya, 2026)
Donggala Regency has substantial coastal and marine resources that can underpin a blue economy. Identifying priority sectors is crucial to ensure regional development is effective, sustainable, and inclusive. This study uses a participatory qualitative approach-interviews, field observations, and GIS-based spatial mapping-combined with Location Quotient (LQ) analysis to assess sectoral specialization against a reference region. Qualitative data were thematically analyzed, and LQ values interpreted to gauge each sector’s economic contribution. Results indicate development potential clustered in three main areas: agropolitan, minapolitan, and marine tourism. Twelve base sectors were identified as significant economic contributors. The highest LQ scores were recorded for agriculture, forestry, and fisheries (2.46); accommodation and food service activities (1.69); and transportation-warehousing (1.26). These sectors form a strategic foundation for ecosystem-based fisheries management, green logistics, enhanced maritime connectivity, and sustainable marine tourism development in Donggala Regency. Policy alignment and stakeholder engagement are recommended to realize these opportunities fully. Keywords: Mapping, Blue Economy, Leading Sector, Location Quotient, Donggala